Aprimorando a compreensão da seleção natural: uma abordagem através de metodologias ativas para a educação no ensino da Biologia - Albuquerque, Dannylson Soares de (2025)
Understanding evolutionary processes is essential for educating scientifically informed citizens. With the implementation of the New High School Curriculum and the adoption of the National Common Curricular Base (BNCC), it has become necessary to revise the approach to core Biology topics, such as Natural Selection, and consider new pedagogical guidelines. Recognizing Natural Selection as a central mechanism in the evolution of species provides a solid foundation for understanding biodiversity and the adaptation of organisms to their environments. This study aimed to develop investigative teaching sequences on Natural Selection, focusing on its main types (directional, stabilizing, and disruptive), by employing active methodologies to promote student agency and critical thinking. The implementation of three teaching sequences involved data collection and analysis, hypothesis formulation, and group discussions. The use of active methodologies to teach Natural Selection and its various types resulted in a deeper and more comprehensive understanding of evolutionary mechanisms among students. They began to recognize Natural Selection as a central process in explaining biodiversity and the adaptation of organisms to their environments and were able to apply these concepts in practical situations, such as the analysis of real or simulated evolutionary scenarios. This work aimed to report on the experience of transforming teaching practices through the application of active methodologies, with an emphasis on inquiry-based learning, Problem- Based Learning (PBL), and gamification. The proposal stemmed from the need to make lessons more meaningful, fostering greater student interest and participation. Through inquiry-based learning, students were observed to shift from a passive to a more active role in constructing knowledge, demonstrating curiosity, engagement, and autonomy. The incorporation of PBL contributed to the development of critical thinking and problem-solving skills by presenting contextualized challenges that required research, reflection, and collaborative work. Gamification, by incorporating playful elements such as scoring, rewards, and levels, increased student motivation and fostered a more participatory and interactive learning environment. The results demonstrated significant improvements in learning, including increased classroom participation, enhanced academic performance, and the development of socio-emotional skills. It is concluded that the adoption of these methodologies fosters more active, autonomous, and meaningful learning, proving to be an effective strategy for educating critical and creative students who are better prepared to face the challenges of contemporary society.